(untitled) (The International Journal of Educational Sciences and Arts, 2024)
The study aimed to identify the mental image presented about the non-profit sector in the Saudi press, through an analytical study applied to a sample of Saudi electronic newspapers consisting of (4) newspapers, namely: (Al-Youm Newspaper - Al-Jazirah - Al-Riyadh - Sabq), during a period of three months according to the (Industrial Week) method, 2024 AD, with a total of (46) newspaper topics. The study belongs to descriptive studies, and relied on the survey method, while the content analysis tool was used as a tool for collecting data. The study reached a set of results, the most important of which are: (Press news) came at the forefront of the journalistic forms used to address topics of the non-profit sector through the Saudi electronic newspapers of the study sample, with a percentage of (87%). (Health) came at the forefront of the topics of the non-profit sector presented in the Saudi electronic newspapers of the study sample, and in second place came the topic (Developing the non-profit sector), followed by (Community Development) in third place, then (Education) in fourth place. In general, it is noted that positive attributes dominate the mental image presented by the Saudi electronic newspapers in the study sample about the non-profit sector in the Kingdom, as the attribute (it has an important societal role) came at the forefront of the positive attributes of the mental image presented about the non-profit sector, and in second place came the attributes (it must be supported) and (its activities are diverse), followed by the attribute (it has high credibility) in third place.